2017
DOI: 10.1111/jocn.14129
|View full text |Cite
|
Sign up to set email alerts
|

Social support and factors associated with self‐efficacy among acute‐care nurse practitioners

Abstract: The findings inform hospital administrators to be aware of the importance of salary in relation to nurse practitioners' perceptions of social support and self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 19 publications
4
37
3
4
Order By: Relevance
“…Thus, nurses' burnout will further be reduced. Additionally, we found that PSS directly, positively affected self‐efficacy with a small effect size (H2), which was consistent with Hu et al's () study results. When nurses perceived that they get support from within or outside the family, they may feel their work is valuable and gain more confidence.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, nurses' burnout will further be reduced. Additionally, we found that PSS directly, positively affected self‐efficacy with a small effect size (H2), which was consistent with Hu et al's () study results. When nurses perceived that they get support from within or outside the family, they may feel their work is valuable and gain more confidence.…”
Section: Discussionsupporting
confidence: 92%
“…The factors influencing PSS may be related to interpersonal sensitivity (Wedgeworth et al, ) or WS (Jin et al, ). Additionally, when nurses experience low levels of PSS, their self‐efficacy will decrease (Hu, Yu, Chang, & Lin, ), while psychological distress (Feng et al, ) will increase. Moreover, Babaeiamiri () studied the influence of nurses' job burnout, PSS and psychological hardiness on nurses' mental health among 400 Iranian nurses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, [22] investigated the relationship monthly salary with perceived self-efficacy in Taiwan using a cross-sectional quantitative survey. The study found out that nurse practitioners in the high monthly salary group had significantly higher self-efficacy than nurse practitioners in the medium and low monthly salary group did.…”
Section: Influence Of Remuneration On Teachers' Self-efficacymentioning
confidence: 99%